Defining sports moral character and clarifying its related concepts - Liu, Cong; Qu, Guofeng; Gao, Rong (Frontiers in Sports and Active Living, 2023)
This study examines the concept of sports moral character and clarifies the differences between it and related moral concepts in sports. The research is conceptual and uses the methods of a literature review and logical analysis. Sports moral character is shown to have the characteristics of practicality, growth, and integration. It is a stable moral quality that is gradually formed and displayed in sports practice under the influence of family, school, and social environments. Sports moral character differs in some ways from other related concepts. Sports morality is the objective existence of “reason,” to which sports character and sportsmanship are both more applicable than is sports moral character.